Characteristics of the Development of Kindergarten-Age Children at Nurul Ihsan Ilmi Kindergarten, Medan Temb - Lubis, Ramadhan; Pasaribu, Sayang; Purba, Wanda Amelia; Berutu, Sri Rahmayanti; Harahap, Hasima; Putri, Devita Aulia; Harahap, Rizki Melinda; Adella, Sindy (Universitas Ibn Khaldun, 2024)
This study aims to describe the characteristics of the development of spirituality of school-age children in Nurul Ihsan Ilmi Kindergarten, Medan Tembung. In this context, spirituality includes moral, religious, and awareness of the meaning of life. This study presents an analysis of how children's spiritual development is affected by various aspects, including physical, intellectual, emotional, social, and moral development. At an early age, known as the golden period of development, children are very sensitive to environmental stimulation, which makes early childhood education an important foundation for their growth. The findings suggest that the integration of spiritual education into the daily curriculum, through concrete activities such as joint prayer and moral stories, provides significant hands-on experience in helping children internalize spiritual values. Therefore, collaboration between teachers, parents, and the school environment is indispensable to ensure holistic and effective spiritual education, supporting the overall development of children.